Spontaneous retinopathy in HLA-A29 transgenic mice - Szpak, Yann (The National Academy of Sciences, 2001)
Humans who have inherited the class I major histocompatibility allele HLA-A29 have a markedly increased relative risk of developing the eye disease termed birdshot chorioretinopathy. This disease affecting adults is characterized by symmetrically scattered, small, cream-colored spots in the fundus associated with retinal vasculopathy and inflammatory signs causing damage to the ocular structures, leading regularly to visual loss. To investigate the role of HLA-A29 in this disease, we introduced the HLA-A29 gene into mice. Aging HLA-A29 transgenic mice spontaneously developed retinopathy, showing a striking resemblance to the HLA-A29-associated chorioretinopathy. These results strongly suggest that HLA-A29 is involved in the pathogenesis of this disease. Elucidation of the role of HLA-A29 should be assisted by this transgenic model.